Severe symptomatic hyperparathyroidism—Is it carcinoma?—Case report and literature review - A. Pereira, Catarina (2020)
Parathyroid carcinoma is a rare disease, difficult to diagnose and associated with a poor prognosis. It must be suspected preoperatively, based on clinical and imaging grounds, in order to perform the best surgical option and avoid compromising patient's prognosis.